Konsep Al-‘Ilm dalam Studi Pemikiran Filsafat Mulla Sadra - Nurul Khair (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2021)
This paper is a literature review of Mulla Sadra's thoughts on the concept of ilm al-ilahī to complement the western epistemological discourse which is considered to eliminate the spiritual aspect in philosophy. This paper aims to explain the meaning, purpose, and urgency of Ilm al-Ilahī to add paradigms and individual behavior in Mulla Sadra's perspective by referring to one of his magnum opus entitled al-Hikmah al-Mutāliyah fī al-Asfār al-Aqliyyah al-Arba'ah. . By using the philosophical descriptive method, it is concluded that al-'Ilm al-Ilah' in Mulla Sadra's philosophical systematics explains the significance of the paradigm and individual behavior to achieve ultimate perfection through the actuality of the soul. The soul in Mulla Sadra's view is the substance of human existence that experiences a movement from potential to actuality by involving the existence of reason and the five senses as the basic building of Islamic epistemology. The result of this paper is that the western epistemological discourse has not yet explained spiritual knowledge in human existence, while Mulla Sadra's significant role is to complete it by adding the spiritual side that is neglected in western discourse.Abstrak: Tulisan ini merupakan telaah pustaka pemikiran Mulla Sadra mengenai konsep ilm al-ilahī untuk menyempurnakan wacana epistemologi barat yang dipandang telah menghilangkan pengetahuan spiritual dalam peradaban filsafat. Tulisan ini bertujuan menjelaskan makna, tujuan, dan urgensi Ilm al-Ilahī untuk menyempurnakan paradigma dan perilaku individu dalam perspektif Mulla Sadra dengan merujuk salah satu magnumopusnya yang berjudul al-Hikmah al-Mutāliyah fī al- Asfār al-Aqliyyah al-Arba’ah. Dengan menggunakan metode deskriptif filosofis dihasilkan kesimpulan bahwa al-‘Ilm al-Ilahī dalam sistematika filsaat Mulla Sadra menjelaskan signifikansi paradigma dan perilaku individu untuk mencapai kesempurnaan hakiki melalui aktualitas jiwa. Jiwa dalam pandangan Mulla Sadra merupakan substansi keberadaan manusia yang mengalami pergerakan dari potensial menuju aktualitas dengan melibatkan eksistensi akal dan pancaindra sebagai bangunan dasar epistemologi Islam. Hasil dari tulisan ini, ialah menyempurnakan wacana epistemologi barat yang dipandang belum menjelaskan pengetahuan spiritual dalam eksistensi manusia melalui studi pemikiran Mulla Sadra.